The Legal Status of Women in Egyptian Constitutions (1923-1971) (Journal of the College of Basic Education, 2025)
Egyptian women have long aspired to regain their long-denied rights, especially since they have suffered from marginalization in all their rights despite the rising calls of intellectuals demanding their rights. Women participated in demonstrations alongside men, particularly during the 1919 Revolution. However, the constitution that emerged from the revolution, the 1923 Constitution, called for women's education. However, it did not affirm their political participation until the 1956 Constitution, which recognized women's right to vote and run for office, and legal equality with men. Women participated in the 1957 elections for the first time as voters and candidates, winning seats in the Egyptian Parliament. Therefore, the 1956 Constitution represented a qualitative leap in women's rights, but significant social and cultural challenges remained that hindered women from continuing to achieve their rights. This was followed by the 1964 Constitution, which was completely similar to the previous constitution. However, Egyptian women did not fully attain their rights until the 1971 Constitution